Risk factors associated with preterm delivery. Cienfuegos 2012 - Aymara Rodríguez Márquez; Esteban Hernández Barrio; Janet Villafuerte Reinante; Zulema Tamara Mesa Montero; Yoan Hernández Cabrera; Ana Margarita López Rodríguez del Rey (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: preterm delivery is a public health problem due to the repercussions on the child´s life, causing 75% of neonatal morbidity and mortality. Objective: to identify risk factors associated with preterm delivery. Methods: descriptive, correlational, cross-sectional study of two case series that included 678 pregnant women from the Cienfuegos province during 2012; out of them a group of 226 who had deliveries between 28 and 36.6 s weeks and another group of 452 with delivery after 37 weeks. Gestational age at admission, risk factors for prematurity, presence of cervical changes to clinical examination and trans-vaginal ultrasound were analyzed. Chi- square was calculated with 95% reliability and the quotient of possibilities. Results: extreme ages and schooling level of between seventh and ninth grades influenced significantly in favor of pregnant women with preterm delivery. Other factors such as smoking, alcohol ingestion, previous preterm pregnancy (OR = 2.32), pre-eclampsia (OR = 6.31), delayed intrauterine growth (OR = 3.77), urinary infections ( OR = 3, 41), and vaginal, premature rupture of membranes and cervical changes (OR> 2), showed highly significant differences in pregnant women with preterm delivery. Conclusions: pre-eclampsia, delayed intrauterine growth and urinary tract infections were the risk factors with the highest possibility ratio for preterm delivery, however there are others that also enhance it. Modifying these factors is determinant for decreasing preterm deliveries.